Menanam Akar, Bukan Daun: Pendidikan Karakter dari Pesantren Darul Ulum Jombang: Pendidikan Karakter dari Pesantren Darul Ulum Jombang - Ahmad, Fandy (DIDAKTIKA : Jurnal Pemikiran Pendidikan, 2026)
The character crisis among Indonesia's younger generation today is not merely a matter of fading morality, but also of a lost sense of direction within an educational landscape increasingly preoccupied with numbers and accolades. This study seeks to rediscover the character values embedded in two classical Islamic texts, Bidayatul Hidayah by Imam al-Ghazali and Ta’lim Muta’allim by Imam az-Zarnuji, and to explore how these values are nurtured in the daily lives of students at Darul Ulum Islamic Boarding School in Jombang. Employing a qualitative approach and thematic analysis, the research reveals that values such as sincerity, discipline, self-restraint, respect for teachers, purity of intention, and perseverance are not merely taught, but are actively embodied through lived habits and role modeling that cultivate growth. The pesantren (Islamic boarding school) emerges as fertile ground where the roots of character are planted, not just the glittering leaves of achievements. In a fast-paced world rife with distraction, pesantren and the classical texts it upholds offer a contemplative space and a deep, nurturing process through which noble character can flourish. This research affirms that the legacy of classical Islamic education remains profoundly relevant in shaping today’s generation, particularly in addressing the moral crisis facing youth in the digital age.